The regulation of inhibitor of apoptosis proteins (IAPs) during the apoptosis of Cotesia chilonis - Lu, Ming-Xing; He, Fu-Jing; Zhu, Feng; Du, Yu-Zhou (Frontiers in Physiology, 2023)
Inhibitor of apoptosis proteins (IAPs) are crucial components of apoptosis that perform vital roles in the regulation of caspase activity in organisms. In this study, two IAPs iap genes were identified from Cotesia chilonis, the dominant parasitic wasp of Chilo suppressalis. CcIAP1 gene is a typical IAP and contains two BIR domains and a RING domainencodes a 1155-bp ORF, whereas CcIAP gene is an atypical IAP1 geneonly containing two BIR domainsa 951-bp ORF; neither Cciap1 or Cciap contain introns. Both CcIAP1 and CcIAP contain two BIR domains; however, only CcIAP1 contains a RING domain. Phylogenetic analysis indicated that CcIAP1CcIAP1 and CcIAP CcIAP were grouped with other Hymenopteran iap genes IAPs and IAP1IAP1 in C. suppressalis. Real-time quantitative PCR revealed that CcIAP1Cciap1 and CcIAP genesCciap were both highly induced at -6 °C and 30 °C, and expression was highest at the 3 rd instar stage. The expression of CcIAP1Cciap1 and CcIAP genesCciap was monitored during parasitism of C. suppressalis, and both genes were significantly induced at 3, 6, 7, 8, and 9 days during parasitism of C. suppressalis of parasitism. The , and the 7-d time point resulted in the highest expression levels for both genes, and in which wascorrelated with an advanced stage of larval development of C. chilonis. RNAi experiments showed that CcIAP1 geneCcIAP1 was the key IAP in the regulation of apoptosis of C. chilonis and its host. In conclusion, CcIAP1 and CcIAPCcIAP1 and CcIAP correlate with the development of C. chilonis and its their responses to temperature stress.